CARACTERISATION PERCEPTIVE DES VARIETES HYBRIDES CHINOISES DU MAÃS : LA SÃ‰LECTIVITÃ‰ SENSORIELLE EST-ELLE DÃ‰TERMINANTE AU BÃ‰NIN ? - Dedehouanou, Houinsou; Affokpon, Antoine; Akissoe, NoÃ«l; Yallou, Chabi G.; Rachidatou, Sikirou; Ahounou, Jean Louis; Badou, Antoine (European Scientific Journal, ESJ, 2015)
Agricultural researches usually advocate high yielding competitive crop varieties in order to supply foodstuff to the increasing population. However, this is not to care for the social dimension of adoption in the technology transfer process. That is why the present paper acknowledges actors like producers, food processors, marketers and others, whose perception with respect to growing, harvesting and processing stages of maize, to be included in the perceptive evaluation of Chinese hybrid varieties at the research centers. Four new varieties of maize are promoted: T2 (Guidan 162), T3 (Jinguyuan 688), T4 (Jinyu No.8) and T5 (Xianyu 335). Actors compare new Chinese varieties of maize to their traditional ones. On the basis of a comparative appraisal index (CAI), ie. a new variety is likely to be adopted if the differences of score between its descriptors and those of the traditional variety are greater than zero. In terms of results, T2 and T4 are the most likely to be adopted in the South and the Center. In the North, on the contrary, T5 is substituted to T4. Because of a low performance on various descriptors, T3 is unlikely to be adopted. While in the south and the center of Benin, sensorial descriptors remain decisive in the adoption profile, agromorphological and harvest stage descriptors are more likely to affect adoption in the North. Based on the increasing economic importance of maize, actorsâ€™ perception in the North significantly matters in the process of adoption of new varieties.